Entretien avec Joane Hétu - Arroyas, Frédérique (Critical Studies in Improvisation / Études critiques en improvisation, 2005)

Y a-t-il des créatrices en musique au Québec ? - Carignan, Nicole; Leblanc (FAMEQ à la une, 2005)

Constructions of Identity in the Life Stories of Emma Albani and Glenn Gould - Elliott, Robin (Journal of Canadian Studies, 2005)
Biographical accounts of musicians have enjoyed widespread popularity since the late-Victorian era. Literary theory has recently held biography to be a literary construct, rather than a factual enterprise. Biographies and music are both governed by narrative structures and help to create a sense of individual and collective/national identity. Biographical accounts of two Canadian musicians—Emma Albani and Glenn Gould—are examined. Both musicians are Canadian national icons, but there are several problematic issues in their life stories: Albani’s elitism, class consciousness, and ambiguous relationship to Canada, and Gould’s eccentricity and uncertain sexual identity. The article examines how these issues have been handled in various auto/biographical accounts of the two musicians.

The Loudspeaker as Instrument: the soundworks of Nancy Tobin - Friz, Ann (Musicworks, 2005)

Violet Balestreri Archer (1913-2000) - Hartig, Linda (Music Reference Services Quarterly, 2005)
Violet Archer, one of Canada's well-known composers, passed away in 2000. This article is meant to add biographical information not previously available and to bring closure to her works list. Selected bibliographical citations are also included.
Keywords: Canadian composers; Violet Balestreri Archer

La contribution des femmes à l’histoire musicale et les compositrices d’aujourd’hui au Québec - Lefebvre, Marie-Thérèse (L'accès des femmes à l'expression musicale. Apprentissage, création, interprétation. Les musiciennes dans la société contemporaine, 2005)

L’art de chanter… au féminin : de la prise de paroles au jeu de références postmodernes - Oberhuber, Andrea (L’accès des femmes à l’expression musicale. Apprentissage, création, interprétation : les musiciennes dans la cité, 2005)